Flexural Behavior of Repaired Reinforced Concrete Beams Due to Corrosion of Steel Reinforcement Using Grouting and FRP Sheet Strengthening - Rudy Djamaluddin; Rita Irmawaty; . Fakhruddin; Kohei Yamaguchi (Salehan Institute of Higher Education, 2024)
One of the common causes of damage to the concrete structures close to the sea line is corrosion on the steel reinforcement in the concrete, which may cause spalling on the concrete cover. This paper presents the results of the simulation of the corroded reinforced concrete beams, which were repaired using the grouting method and FRP strengthening. The concrete cover of the beam specimens on the tensile side was filled with grouted concrete instead of filled with normal concrete to simulate the repair of concrete spalling. Three types of beam specimens were prepared and tested under a monotonic loading. BG and BPF were the specimens for beams with grouting only and beams with grouting and flexural strengthening using FRP sheets, respectively. Flexural strengthening using FRP sheets was carried out to restore the flexural capacity. As a comparison, control beams were also prepared in the form of normal reinforced concrete (BN). The results showed that the BG beam had a capacity of only about 50% compared to the control beam (BN). However, applying flexural strengthening using FRP sheet as on the type BGF beams showed that it had approximately the same capacity as BN specimens. This indicated that the repair method using grouting on damaged concrete covers and strengthening using FRP sheets was an effective alternative to repairing the corroded reinforced concrete beams. Doi: 10.28991/CEJ-2024-010-01-014 Full Text: PDF